A Supramolecular Polymerization Approach to the Growth of the Myofibril - Ciferri, Alberto; Crumbliss, Alvin L. (Frontiers in Chemistry, 2019)
Extended linear structures self-assemble by the multi-stage-open-association mechanism of supramolecular polymerization (MSOA). Application of the model requires the identification of a repeating unit, the main-chain supramolecular bond, and the binding constant. The strength of the bond and the degree of polymerization become extremely large when multiple sites for non-covalent interactions occur. These expectations had been previously verified in the case of the neuronal axon, for which the above parameters were assessed from its known molecular structure. The more complex case of the myofibril is analyzed here. The specific interactions that connect neighboring sarcomers have been a matter of debate. Recent work has focused on the bond between titin and α-actinin localized at the terminal Z-zones of each sarcomer. Elaboration of literature data suggests that titin-α-actinin interactions do bridge neighboring sarcomers, promoting the polymerization of myofibrils that attain macroscopic dimensions consistently with the MSOA predictions. The rationale for the complex structuration of single sarcomers is discussed.